Characteristics of E-cigarette or vape (ECV) users and patterns of use: Malaysia chapter - Ab Rahman, Norny Syafinaz; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Kartiwi, Mira; Draman, Samsul; Shafie, Asrul Akmal; Daud, Aziah; Yasin, Siti Munira; Anselm, Su Ting; Robinson, Fredie; Tee, Guat Hiong (Malaysia Medical Association, 2017)
The use of e-cigarette or vape (ECV) is increasing rapidly internationally and also nationally. However, the characteristics of ECV users and patterns of its use in Malaysia are still scarce. Objectives: To explore and assess characteristics and patterns of e-cigarette or vape (ECV) use in Malaysia. Methods: Data were obtained from National E-Cigarette Survey (NECS) 2016 which used a multi-stage stratified cluster sampling household survey representing all Malaysian adults aged 18 years at national and urban/rural level. A total of 4,288 adultsóÂ from all the states were selected and weighted using complex sampling method to represent 19 million Malaysians. Further analyses among current ECV users were conducted to evaluate the characteristics and patterns of ECV used. Results: The majority of current ECV users are 25-44 years old (55.3%), males (95%) and Malays (74.9%). About 86.5% started to use ECV at the age of 19 years and above. A quarter of current ECV users were daily users. Overall, the main reason to use ECV was to experiment (47.0%, 95%CI=38.1 - 56.0) and 55% of current ECV users shared their ECV liquid, mainly among friends. Most of the current ECV users preferred third generation devices or mechanical mods (71.9%, 95%CI=58.6 - 82.3). The mean frequency of ECV use was 18.6 session/day with mean of 16.2 puff per ECV session. Majority (83.9%) preferred ECV liquid with nicotine and the preferred nicotine strength among ECV users was 7.3-mg/ ml. The most favourite places for ECV use were outside (25.3%) and inside (19.1%) of the homes, followed by restaurants without airconditioning (17.5%) and workplaces (16.3%). Conclusions: More education and awareness campaigns towards ECV use should target children as young as school age. Moreover, Malaysia tobacco-free policies should include prohibition of ECV use in public places and workplaces.